Matrimonio, familia y unitarismo: condicionantes sociopolíticos de la doctrina católica en la construcción de la identidad política y jurídica de la familia en Colombia. (2015)
The article explores the tensions between the unitary perspective of family and traditional marriage in Colombia, and legal trends that are diversifying this version, to the point of establishing a conceptual stage of social, cultural and legal crisis related to the veyy family paradigm. It develops this way: i) Description of catholic doctrinal concept of family; ii) influence of the catholic doctrine in the unitarian effort; iii) regeneration; iv) socio-legal hegemony of the paradigm of catholic religion as a hegemonic socio-legal characteristic; v) the relationship between Catholic doctrine and what is expressed by the Colombian legal system regarding the family vi) the legal and jurisprudential debate that has been generated regarding the unitary paradigm of the family; and finally vii) the familiar paradigm change in the legal context.